Critical citizens : global support for democratic government - Norris, Pippa (Oxford scholarship online., 1999)
Critical Citizens is a study on attitudes towards nation, governance, political institutions and political leadership. The contributors argue that the crisis in global democracy has been greatly exaggerated in recent years.